KUALITAS HIDUP LANSIA: KAITANNYA DENGAN INTEGRITAS DIRI, INTERAKSI SUAMI-ISTRI, DAN FUNGSI KELUARGA - Putri, Dwi Kurniati; Krisnatuti, Diah; Puspitawati, Herien (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2019)
Married elderly women will have difficulty to feel the meaningfulness of life if not supported by the functioning of the family and the good interactions between husband and wife. This study aims to analyze the influence of older adults sociodemographic, family characteristics, self integrity, husband-wife interaction, and family functions on quality of life of older adults. Samples of this study were older women aged 60 years old, who lived in rural (Nanggung Sub-District, Bogor Regency) and urban (West Bogor Sub-District, Bogor City), married, and lived in their own house or no-coresidence with children, and an amount of 120 older women. The technique of selecting respondents using simple random sampling. The result of T-tests show that the function of elderly families in urban areas is higher than in rural areas. Dimensions of religion, affection, economic, and environmental development function in elderly families in urban areas is higher than in rural areas. There were significant differences in the functions of independence, control over life and freedom, home and neighbourhood, psychological and emotional well-being, financial circumstances, leisure and activities between the older adults in rural and urban areas. The quality of life of older adults in urban areas was higher than the older adults in rural areas. Quality of life of older adults was significantly influenced by length of wife education, number of chronic illness, revenue per capita, and family function.